Rhythm in language acquisition. (October 2017) - Langus, Alan; Mehler, Jacques; Nespor, Marina
Highlights: The rhythm of spoken language is structured hierarchically. Rhythm is universal on the segmental level, the level of metric feet and phonological phrases. Human infants are sensitive to speech rhythm early in development and may use this sensitivity for breaking into the speech code. Abstract: Spoken language is governed by rhythm. Linguistic rhythm is hierarchical and the rhythmic hierarchy partially mimics the prosodic as well as the morpho-syntactic hierarchy of spoken language. It can thus provide learners with cues about the structure of the language they are acquiring. We identify three universal levels of linguistic rhythm – the segmental level, the level of the metrical feet and the phonological phrase level – and discuss why primary lexical stress is not rhythmic. We survey experimental evidence on rhythm perception in young infants and native speakers of various languages to determine the properties of linguistic rhythm that are present at birth, those that mature during the first year of life and those that are shaped by the linguistic environment of language learners. We conclude with a discussion of the major gaps in current knowledge on linguistic rhythm and highlight areas of interest for future research that are most likely to yield significant insights into the nature, the perception, and the usefulness of linguistic rhythm.